HYPERTENSION KNOWLEDGE AND SELF-MANAGEMENT AMONG OLDER ADULTS AT GROGOL COMMUNITY HEALTH CENTER - Atika Laila Salsabilla; Agus Sudaryanto (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Hypertension is a global health problem with high prevalence and serious complication risks. The elderly are a vulnerable group, with a prevalence of hypertension reaching 34.1% in the Indonesian elderly population. This study aims to analyze the relationship between knowledge levels and self-management in elderly people with hypertension in the Grogol Community Health Center area. The study used a cross-sectional design with a sample of 382 elderly people with hypertension aged ≥ 60 years selected through cluster random sampling. The research instruments had been tested for validity (Pearson Product Moment) and reliability (Cronbach's Alpha 0.807 for knowledge; 0.817 for self-management). The results showed the distribution of knowledge levels: good 16.2%, adequate 51.0%, poor 32.7%; and self-management: good 4.7%, adequate 77.2%, poor 18.1%. The Chi-Square test showed a significant relationship between knowledge and self-management (χ² = 40.251; p = 0.001) with a weak to moderate strength of relationship (Cramer's V = 0.229). These findings indicate that health education needs to be strengthened so that hypertension management can be more optimal.